Laminated film and method for manufacturing the same

JP2026143510APending Publication Date: 2026-09-08DAICEL MIRAIZU LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026090141
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、高湿度環境下においてガスバリア性の低下をより抑制することができる積層フィルム及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026143510000001
    Figure 2026143510000001
Patent Text Reader

Abstract

To provide a laminated film that can further suppress the deterioration of gas barrier properties under high humidity conditions. [Solution] A base layer and A first layer laminated on at least one surface of the substrate layer, A second layer is laminated on the preceding layer, The substrate layer contains a thermoplastic resin, The aforementioned first layer contains a water-soluble vinyl polymer as its main component, The sodium salt concentration in the above layer is less than 0.2% by weight, A laminated film wherein the second layer comprises at least one selected from metals and inorganic oxides as a main component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to laminated films and methods for manufacturing the same. [Background technology]

[0002] Conventionally, gas barrier films are known in which a laminated film with gas barrier properties is formed on a base film to suppress the permeation of oxygen, water vapor, etc. To further improve gas barrier properties, laminated films are known in which a vapor-deposited layer of metal or inorganic oxide is provided on top of the gas barrier laminated film.

[0003] For example, Patent Document 1 proposes improving the adhesion between the vapor-deposited film and the multilayer substrate layer, thereby improving gas barrier properties, by providing a multilayer substrate layer in which a resin material having polar groups is provided as a coating layer on top of a stretched polypropylene resin layer. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2021-024136 [Overview of the project] [Problems that the invention aims to solve]

[0005] However, conventional laminated films with metal or inorganic oxide vapor-deposited films have a problem in that the vapor-deposited film is prone to degradation, especially when stored in high-humidity environments, which reduces its gas barrier properties.

[0006] This disclosure aims to provide a laminated film and a method for manufacturing the same that can further suppress the deterioration of gas barrier properties in high humidity environments. [Means for solving the problem]

[0007] After careful consideration, the inventors of this application found that A base layer and A first layer laminated on at least one surface of the substrate layer, A second layer is laminated on the preceding layer, The substrate layer contains a thermoplastic resin, The aforementioned first layer contains a water-soluble vinyl polymer as its main component, The sodium salt concentration in the above layer is less than 0.2% by weight, We found that the above problem can be solved if the second layer is a laminated film in which at least one selected from metals and inorganic oxides is used as the main component. [Effects of the Invention]

[0008] According to this disclosure, it is possible to provide a laminated film and a method for manufacturing the same that can further suppress the deterioration of gas barrier properties in a high humidity environment. [Modes for carrying out the invention]

[0009] One embodiment of this disclosure will be described in detail below, but the scope of this disclosure is not limited to the embodiment described herein, and various modifications can be made without departing from the spirit of this disclosure. Each embodiment disclosed herein can be combined with any other features disclosed herein. Furthermore, if multiple upper and lower limits are described for a particular parameter, any combination of these upper and lower limits can be used to create a suitable numerical range. Also, the lower and / or upper limits of the numerical ranges described herein may be replaced with numerical values ​​within that range, as shown in the examples. The expression "X~Y" indicating a numerical range means "X or more and Y or less". Furthermore, unless otherwise noted, all test temperatures are room temperature (20℃±5℃). If a specific description given for one embodiment also applies to other embodiments, that description may be omitted in the other embodiments.

[0010] Each configuration and combination thereof in each embodiment is an example, and additions, omissions, substitutions, and other modifications are possible as appropriate, without departing from the spirit of this disclosure. This disclosure is not limited by the embodiments, but is limited only by the claims. Each aspect disclosed herein can be combined with any other features disclosed herein.

[0011] [Laminated film] A first embodiment of this disclosure relates to a laminated film. The laminated film according to the first embodiment is A base layer and A first layer laminated on at least one surface of the substrate layer, A second layer is laminated on the preceding layer, The substrate layer contains a thermoplastic resin, The aforementioned first layer contains a water-soluble vinyl polymer as its main component, The sodium salt concentration in the above layer is less than 0.2% by weight, The second layer comprises at least one selected from metals and inorganic oxides as its main component. According to the laminated film of the first embodiment, a packaging film can be provided that can further suppress the decrease in gas barrier properties in a high humidity environment. Water-soluble vinyl polymers are water-soluble synthetic resins that were traditionally used mainly as raw materials for synthetic fibers. However, in recent years, their unique properties have led to their use in various fields such as film materials, emulsifiers and dispersants, adhesives, and binder resins. These water-soluble vinyl polymers are produced by polymerizing vinyl acetate monomer and saponifying the resulting polyvinyl acetate. The resulting water-soluble vinyl polymers typically contain sodium salts (especially sodium acetate). The present inventors have conducted intensive research and found that by reducing the sodium salt concentration in a layer containing a water-soluble vinyl polymer as a main component, degradation of a layer containing at least one selected from metals and inorganic oxides can be further suppressed. This enables obtaining a laminated film that can further suppress a decrease in gas barrier properties under high-humidity environments.

[0012] <Base material layer> The base material layer contains a thermoplastic resin. That is, the base material layer is formed of a resin composition containing a thermoplastic resin (hereinafter may also be referred to as "resin composition for base material layer"). (Thermoplastic Resin) Examples of the thermoplastic resin include polyolefin resins (polyethylene, polypropylene, etc.), polyester resins (polyethylene naphthalate, polyethylene terephthalate, etc.), polyamide resins (nylon-6, nylon-66, etc.), polystyrene, ethylene-vinyl alcohol copolymer resins, polyvinyl chloride, polyimide, polyvinyl alcohol, polycarbonate, polyether sulfone, acrylic resins, and cellulose resins (triacetyl cellulose, diacetyl cellulose, etc.). These thermoplastic resins may be used alone, or two or more of them may be used in combination. In one embodiment, the thermoplastic resin is preferably a polyolefin resin. In one embodiment, the base material layer is preferably a film formed of a polyolefin resin.

[0013] Examples of polyolefin resins include polyethylene resins, polypropylene resins, and the like.

[0014] Examples of polyethylene resins include low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA) resin, ethylene-α-olefin copolymer resin, ethylene-(meth)acrylic acid copolymer resin, and the like.

[0015] Examples of polypropylene resins include homopolypropylene resins, block polypropylene resins, random polypropylene resins, and copolymer resins of propylene and other monomers. Examples of other monomers include α-olefins such as ethylene, 1-butene, 1-hexene, 1-octene, 3-methylpentene, and 4-methylpentene. The polypropylene resin may also be a copolymer resin obtained by combining two or more other monomers with propylene. When the substrate layer contains the copolymer resin, it is preferable that the monomer component contains 80% by mass or more of propylene, more preferably 90% by mass or more, preferably 95% by mass or more, and particularly preferably 98% by mass or more.

[0016] Furthermore, the polypropylene resin may have an atactic structure, an isotactic structure, a syndiotactic structure, or a metallocene structure.

[0017] In one embodiment, the base layer is preferably a polypropylene resin film (particularly a homopolypropylene film). This film may be a uniaxially oriented film, a biaxially oriented film, or an unoriented film. The base layer may also consist of a single film or a laminate of two or more films. If the base layer is a laminate of two or more films, the types of polyolefin resins contained in each layer may be the same or different. In one embodiment, the base layer is preferably a biaxially oriented polypropylene (OPP) film.

[0018] Furthermore, the polyolefin resin contained in the base layer may be a polyolefin resin derived from biomass, or a polyolefin resin that has been mechanically or chemically recycled.

[0019] (Additives) The resin composition for the base layer may contain known additives such as antioxidants, weather stabilizers, heat stabilizers, lubricants, nucleating agents, ultraviolet absorbers, colorants, and antiblocking agents, to the extent that the effects described herein are not hindered. For example, at least one resin selected from petroleum resins and terpene resins may be added to improve the water vapor barrier properties of the base layer. If the base layer contains these resins, their total content may be 1% by mass or more, 2% by mass or more, 15% by mass or less, or 10% by mass or less, based on the total mass of the resin composition for the base layer.

[0020] Furthermore, to improve the adhesion between the substrate layer and the first layer, corona discharge treatment, plasma treatment, etc., may be performed on the surface of the substrate layer. If necessary, corona discharge treatment or plasma treatment may also be performed on the surface where the first layer is not laminated (the uncoated side).

[0021] The thickness of the base layer is not particularly limited and can be set appropriately depending on the application of the packaging film. In one embodiment, the thickness of the base layer may be 5 μm or more, 10 μm or more, or 15 μm or more. The upper limit of the thickness of the base layer may be 100 μm or less, 90 μm or less, or 80 μm or less. In other words, the thickness of the base layer may be 5 to 100 μm, 10 to 90 μm, or 15 to 80 μm. In one embodiment, the base layer is preferably a biaxially oriented polypropylene (OPP) film with a thickness of 5 to 80 μm.

[0022] <First layer> The laminated film according to the first embodiment comprises a first layer laminated on at least one surface of the substrate layer, the first layer comprising a water-soluble vinyl polymer as its main component. That is, the first layer is composed of a resin composition comprising a water-soluble vinyl polymer as its main component. Alternatively, the first layer may be laminated on a surface of the substrate layer that has been treated with corona discharge or plasma. In the first embodiment, the first layer contains a water-soluble vinyl polymer as its main component. In this specification, "main component" means a component that is present in more than 50% by mass of the total mass (100% by mass). In one embodiment, it is preferable that the water-soluble vinyl polymer accounts for 60% by mass or more of the components constituting the first layer, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In one embodiment, the first layer is preferably a film composed of a resin mainly containing a water-soluble vinyl polymer, and more preferably a film composed of a resin made of a water-soluble vinyl polymer. By including such a first layer, a packaging film can be obtained that has high gas barrier properties due to the low oxygen permeability and moisture permeability, which are characteristics of water-soluble vinyl polymers, and can further suppress the decrease in gas barrier properties in high humidity environments.

[0023] (Water-soluble vinyl polymer) In this embodiment, the water-soluble vinyl polymer is a water-soluble resin that includes a polymer obtained by polymerizing monomers having vinyl groups. Examples of water-soluble vinyl polymers include vinyl alcohol polymers. Examples of vinyl alcohol polymers include homopolymers such as polyvinyl alcohol and olefin-vinyl alcohol copolymers such as olefin-modified polyvinyl alcohol (e.g., ethylene-vinyl alcohol copolymers). 2-10 (preferably C 2-5 , more C 2-3 Examples include olefin-vinyl alcohol copolymers. These water-soluble vinyl polymers can be used individually or in combination of two or more. In one embodiment, from the viewpoint of gas barrier properties, the water-soluble vinyl polymer preferably contains an olefin-modified vinyl alcohol resin, and more preferably contains a polyvinyl alcohol (PVA) resin and / or an olefin-vinyl alcohol copolymer. From the viewpoint of gas barrier properties in a high humidity environment, the water-soluble vinyl polymer preferably contains an olefin-vinyl alcohol copolymer, C 2-10 (preferably C2-5 , more C 2-3 It is more preferable to include an olefin-vinyl alcohol copolymer, and even more preferable to include an ethylene-vinyl alcohol copolymer.

[0024] The degree of saponification of the vinyl alcohol polymer can be selected from a range of 80 mol% or more, but is preferably 96 mol% or more, more preferably 99 mol% or more (particularly 99.5 mol% or more). The degree of polymerization of the vinyl alcohol polymer is, for example, 200 or more (e.g., 200 to 5000), preferably 300 to 5000, and more preferably 400 to 3000.

[0025] (Sodium salt concentration) In the first embodiment, the first layer contains a water-soluble vinyl polymer as its main component, and the sodium salt concentration in the first layer is less than 0.2% by weight. In this disclosure, "sodium salt concentration in the first layer" means the concentration of sodium salts (particularly sodium acetate) derived from the water-soluble vinyl polymer contained in the first layer, and sodium salts not derived from the water-soluble vinyl polymer are not included in the concentration. By having a sodium salt concentration in the first layer of less than 0.2% by weight, the deterioration of the layer containing at least one selected from metals and inorganic oxides is further suppressed. The sodium salt concentration in the first layer can be reduced to less than 0.2% by weight by using a water-soluble vinyl polymer with a low concentration of sodium salts (particularly sodium acetate) as the raw material water-soluble vinyl polymer. The preparation of the sodium salt concentration in the water-soluble vinyl polymer is described below. The sodium salt concentration in the first layer can be determined by separating the first layer from the laminated film using physical or chemical methods, and then determining the aqueous solution obtained by dissolving the first layer using liquid chromatography or the like. In one embodiment, the sodium salt concentration in the first layer is preferably less than 0.15% by weight, more preferably less than 0.1% by weight, and even more preferably less than 0.05% by weight. In one embodiment, the sodium acetate concentration in the first layer is preferably less than 0.15% by weight, more preferably less than 0.1% by weight, and even more preferably less than 0.05% by weight.

[0026] In one embodiment, the first layer preferably further contains a polyalkyleneimine. The inclusion of a polyalkyleneimine in the first layer improves the adhesion between the substrate layer and the first layer, and further enhances the gas barrier properties. The polyalkyleneimine can be obtained by polymerizing one or more alkyleneimines having 2 to 6 carbon atoms by conventional methods. Examples of alkyleneimines having 2 to 6 carbon atoms include ethyleneimine, propyleneimine, 1,2-butyleneimine, 2,3-butyleneimine, and 1,1-dimethylethyleneimine. In one embodiment, the polyalkylene imine is preferably polyethyleneimine or polypropyleneimine, and more preferably polyethyleneimine. Polyethyleneimine is obtained by polymerizing ethyleneimine and has a branched chain structure containing primary, secondary, and / or tertiary amine nitrogen atoms in its structure.

[0027] The weight-average molecular weight of the polyalkyleneimine is measured by gel permeation chromatography (GPC) and is preferably 1,000 to 1,000,000, more preferably 10,000 to 300,000, even more preferably 30,000 to 100,000, and particularly preferably 50,000 to 80,000.

[0028] In one embodiment, the thickness of the first layer is preferably 0.2 to 4.0 μm, more preferably 0.2 to 2.0 μm, even more preferably 0.4 to 2.0 μm, and particularly preferably 0.4 to 1.5 μm.

[0029] In one embodiment, an anchor coat layer may be formed between the base layer and the first layer. The anchor coat layer can be formed by applying an anchor coat agent to the base layer. Conventional known anchor coat agents can be used as the anchor coat agent, and anchor coat agents for food packaging films are particularly preferred. From the viewpoint of easily achieving the effects of this disclosure, it is preferable to have a configuration in which the first layer is directly laminated on the base layer.

[0030] In one embodiment, the first layer may further contain a layered inorganic compound. Examples of the layered inorganic compound include swollen hydrated silicates, such as smectite group clay minerals (montmorillonite, beidelite, nontronite, saponite, hectorite, souconite, stevensite, etc.), vermiculite group clay minerals (vermiculite, etc.), kaolin-type minerals (haloysite, kaolinite, endelite, dickite, etc.), phyllosilicates (talc, pyrophyllite, mica, margalite, muscovite, phlogopite, tetrasilicic mica, teniolite, etc.), jamonite group minerals (antigorite, etc.), and chlorite group minerals (chlorite, cookite, nanthite, etc.). These layered inorganic compounds may be natural or synthetic. These layered inorganic compounds can be used alone or in combination of two or more. Among these layered inorganic compounds, smectite group clay minerals, particularly montmorillonite, are preferred.

[0031] <Second layer> The second layer is a layer directly laminated on top of the first layer. In this disclosure, "directly laminated" means that there are no other layers between the first and second layers. However, if necessary, other layers may be laminated on top of the second layer.

[0032] The second layer contains, as a main component, at least one selected from metals and inorganic oxides. The definition of "main component" is as described above. In one embodiment, among the components constituting the second layer, the metal or inorganic oxide preferably accounts for 60% by mass or more, more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 80% by mass or more. In one embodiment, the second layer is preferably a vapor-deposited film containing at least one selected from metals and inorganic oxides as a main component, and more preferably a vapor-deposited film consisting of at least one selected from metals and inorganic oxides. Aluminum is preferable as the metal contained in the second layer. Metal oxides are preferable as the inorganic oxide contained in the second layer. Preferable examples include aluminum oxide, silicon oxide, magnesium oxide, tin oxide and the like. Among these, the second layer is preferably a vapor-deposited film containing, as a main component, at least one selected from aluminum oxide and silicon oxide, and is particularly preferably a vapor-deposited film containing aluminum oxide as a main component. In the present disclosure, aluminum oxide is AlO x (0 < x ≤ 1.5), and silicon oxide is SiO x (0 < x ≤ 2.0). The second layer may contain elements other than aluminum oxide and silicon oxide within a range that does not impair the effects of the present disclosure. In one embodiment, the second layer is preferably a vapor-deposited film containing, as a main component, at least one selected from aluminum, aluminum oxide and silicon oxide, and more preferably a vapor-deposited film containing aluminum as a main component. In one embodiment, the second layer is preferably a layer containing vapor-deposited aluminum, and more preferably a layer consisting of vapor-deposited aluminum.

[0033] From the viewpoint of gas barrier properties, the thickness of the second layer is preferably 3 nm or more, more preferably 10 nm or more, and still more preferably 30 nm or more. Further, the upper limit thereof is preferably 300 nm or less, more preferably 100 nm or less. When the second layer is a vapor-deposited film, the thickness of the second layer can be adjusted by the vapor deposition conditions described later. From the viewpoint of gas barrier properties, the total thickness of the laminated film is preferably 5 to 104 µm, more preferably 5 to 100 µm, even still more preferably 5 to 90 µm, and particularly preferably 10 to 80 µm.

[0034] <Protective layer> The laminated film according to the first embodiment may further include a protective layer. The protective layer is a layer laminated on the second layer. Providing the protective layer facilitates further improvement of the gas barrier properties of the laminated film. The protective layer may contain, for example, a water-soluble polymer such as polyvinyl alcohol-based resin, polysaccharides such as starch, methylcellulose and carboxymethylcellulose, hydroxyl group-containing polyacrylic resin, or the like; polyurethane-based resin; polyester-based resin; acrylic resin; titanium-based resin; isocyanate-based resin; imine-based resin; polybutadiene-based resin; and the like. These may be used alone, or two or more of these may be used in combination. Further, these resins and a curing agent may be used in combination.

[0035] In one embodiment, from the viewpoint of easily improving the adhesion between the second layer and the protective layer, the protective layer preferably contains a polyurethane-based resin. As the polyurethane-based resin, the same resin as the above-mentioned polyurethane resin (A) may be used, or a different polyurethane resin may be used.

[0036] In one embodiment, from the viewpoint of easily improving gas barrier properties, the protective layer comprises a water-soluble polymer and a compound represented by the general formula: M(OR) nIt is preferable to include a metal alkoxide represented by and / or its hydrolysate, and more preferably to include a water-soluble polymer and a siloxane compound in which M in the above general formula is silicon. The water-soluble polymer preferably includes a polyvinyl alcohol-based resin.

[0037] The thickness of the protective layer is not particularly limited as long as it achieves the effects of this disclosure, but it is preferably 0.1 to 1 μm. If the laminated film further includes a protective layer, the overall thickness of the laminated film is preferably 5 to 104 μm, more preferably 5 to 100 μm, even more preferably 5 to 90 μm, and particularly preferably 10 to 80 μm, from the viewpoint of gas barrier properties.

[0038] <Application> As described above, the laminated film according to the first embodiment can further suppress the decrease in gas barrier properties in a high-humidity environment. Such a laminated film can be suitably used as a packaging film for various packaging applications where gas barrier properties are required in a high-humidity environment, such as a packaging film for food packaging. In one embodiment, the laminated film according to the first embodiment is preferably a packaging film.

[0039] [Method for manufacturing laminated film] A second embodiment of this disclosure relates to a method for manufacturing a laminated film according to the first embodiment. The manufacturing method according to the second embodiment includes laminating a first layer onto at least one surface of a base layer (step (1)) and laminating a second layer on the first layer (step (2)). The following describes an example of a manufacturing method including steps (1) and (2).

[0040] <Process (1): Lamination of the first layer> Step (1) is a step of laminating the first layer onto at least one surface of the substrate layer. In one embodiment, the lamination step is preferably carried out by preparing a coating agent containing a water-soluble vinyl polymer as the main component and applying the coating agent to the substrate layer. In one embodiment, a preparation step for the coating agent (step (1')) may be included before step (1).

[0041] (Step (1'): Preparation of coating agent) The coating agent can be prepared, for example, by adding a predetermined amount of a water-soluble vinyl polymer to water and mixing. The solid content concentration in the coating agent can be within any range, but in one embodiment, the solid content concentration in the coating agent is preferably 5 to 20%. To adjust the sodium salt concentration in the first layer to less than 0.2% by weight, a commercially available water-soluble vinyl polymer that has undergone sodium salt (especially sodium acetate) reduction treatment may be used as the water-soluble vinyl polymer used in the coating solution. Alternatively, since sodium salt (especially sodium acetate) dissolves in polar solvents such as methanol and water, the sodium salt (especially sodium acetate) concentration in the water-soluble vinyl polymer can be reduced by washing the commercially available water-soluble vinyl polymer with methanol or water and then separating the water-soluble vinyl polymer from the washing solution by filtration or other methods, thereby moving the sodium salt (especially sodium acetate) into the filtrate.

[0042] The obtained coating agent is applied onto a substrate layer. It is preferable to use the aforementioned film as the substrate layer to which the coating agent is applied. In one embodiment, the substrate layer is preferably a polypropylene resin film, and more preferably a biaxially oriented polypropylene (OPP) film.

[0043] The amount of coating agent applied (weight of the first layer after drying) can be appropriately selected according to the size of the substrate layer, the desired thickness of the first layer, etc. In one embodiment, the amount of coating agent applied (weight of the first layer after drying) is 0.2 to 5.0 g / m². 2 Preferably, it is 0.5 to 2.4 g / m 2 It is more preferable that the amount be 0.5 to 1.8 g / m 2 It is even more preferable that it be so.

[0044] The method for applying the coating agent to the substrate layer is not particularly limited, and known methods and apparatus such as gravure coating, reverse coating, doctor coating, bar coating, and dip coating can be used.

[0045] By heat treatment after coating, the first layer is formed on at least one surface of the substrate layer as the solvent evaporates, and the first layer is laminated on the substrate layer. The temperature of the heat treatment may be, for example, 80°C or higher, 90°C or higher, or 100°C or higher. The upper limit may be 140°C or lower, or 120°C or lower. The time of the heat treatment can be appropriately changed depending on the type of solvent, the amount coated, and the temperature.

[0046] In one embodiment, an aging treatment may be performed after the heat treatment. The temperature of the aging treatment may be 40°C or higher, and may be 50°C or higher. The upper limit may be 60°C or lower. The duration of the aging treatment may be, for example, one day or more.

[0047] <Process (2): Lamination of the second layer> Step (2) involves laminating a second layer on the first layer obtained in step (1), the second layer containing at least one selected from metals and inorganic oxides as its main component. From the viewpoint of easily obtaining a laminated film with excellent gas barrier properties, the second layer is preferably a vapor-deposited film containing at least one selected from metals and inorganic oxides, and more preferably a vapor-deposited film consisting of at least one selected from metals and inorganic oxides. The metals and inorganic oxides mentioned above can be used. In one embodiment, the metal contained in the second layer is preferably aluminum. In one embodiment, the second layer is preferably a layer containing vapor-deposited aluminum, and more preferably a layer consisting of vapor-deposited aluminum.

[0048] The deposition method is not particularly limited, and known methods and apparatus can be used. It may be physical vapor deposition (PVD) or chemical vapor deposition (CVD). Examples of physical vapor deposition methods include vacuum deposition, reactive deposition, sputtering, reactive sputtering, ion plating, and reactive ion plating. Examples of chemical vapor deposition methods include plasma CVD and laser CVD. The deposition conditions may be appropriately selected to obtain a second layer of the desired thickness.

[0049] <Process (3): Lamination of protective layer> In the manufacturing method according to this embodiment, the process may further include laminating a protective layer on the second layer (step (3)). The protective layer may be formed by coating the second layer with a coating agent containing a protective layer resin composition comprising the aforementioned resin, or a protective layer resin composition comprising a water-soluble polymer and a metal alkoxide and / or its hydrolysate. The coating agent may contain a solvent or dispersion medium. The same method as exemplified in step (1) can be used as the coating method.

[0050] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of this disclosure is provided below. [1] Substrate layer and A first layer laminated on at least one surface of the substrate layer, A second layer is laminated on the preceding layer, The substrate layer contains a thermoplastic resin, The aforementioned first layer contains a water-soluble vinyl polymer as its main component, The sodium salt concentration in the above layer is less than 0.2% by weight, A laminated film wherein the second layer comprises at least one selected from metals and inorganic oxides as a main component. [2] The laminated film according to [1], wherein the second layer is a vapor-deposited film mainly composed of at least one selected from aluminum, aluminum oxide, and silicon oxide. [3] The laminated film according to [1] or [2], wherein the water-soluble vinyl polymer comprises an olefin-modified vinyl alcohol resin. [4] A laminated film according to any one of [1] to [3], wherein the first layer comprises a polyalkyleneimine. [5] The laminated film according to any one of [1] to [4], wherein the thermoplastic resin is a polyolefin resin. [6] A laminated film according to any one of [1] to [5], wherein the thickness of the first layer is 0.2 to 4.0 μm. [7] The laminated film according to any one of [1] to [6] further comprising a protective layer laminated on the second layer. [8] A laminated film according to any one of [1] to [7], which is a packaging film. A method for manufacturing a laminated film according to any one of [9][1] to [8], Laminating the first layer onto at least one surface of the substrate layer, A manufacturing method comprising laminating the second layer on the first layer.

[10] The manufacturing method according to [9], wherein the sodium salt concentration in the first layer is less than 0.2% by weight. [Examples]

[0051] The effects of this disclosure will be demonstrated below by the examples provided, but this disclosure should not be interpreted restrictively based on the description of these examples.

[0052] [Manufacturing of laminated films] [Example 1] Five parts by mass of olefin-modified polyvinyl alcohol resin (manufactured by Kuraray Co., Ltd., ethylene-modified polyvinyl alcohol resin, "Exceval® AQ-4104", sodium acetate concentration: 0.01% by weight) were added to 100 parts of distilled water, and then stirred at 90°C for 1 hour to dissolve. Furthermore, 0.2 parts by mass of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., "Epomin P-1000 (product name)", weight-average molecular weight: 70000, solid content concentration: 30% by mass) were added to prepare a coating solution with a solid content concentration of 5% by weight. A biaxially oriented polypropylene (OPP) film (thickness: 20 μm) treated with corona discharge was prepared as the base layer. The coating solution was applied to the corona discharge treated surface of this base layer using a bar coater to a thickness of 0.5 μm after drying, and then dried in a 100°C oven for 1 minute to form the first layer. Aluminum was directly deposited onto the surface of the first layer by physical vapor deposition (PVD) to form a second layer of vapor-deposited aluminum with a thickness of 50 nm, thereby obtaining the laminated film of Example 1. The laminated film of Example 1 has the following configuration. • Substrate layer: Biaxially oriented polypropylene (OPP) film layer (thickness: 20 μm) • First layer: Olefin-modified polyvinyl alcohol (low sodium acetate) layer (thickness: 0.5 μm), sodium acetate concentration: 0.01% by weight • Second layer: Vapor-deposited aluminum layer (thickness: 50 nm)

[0053] [Comparative Example 1] Five parts by mass of olefin-modified polyvinyl alcohol resin (manufactured by Kuraray Co., Ltd., "Exceval® HR-3010", sodium acetate concentration: 1 wt%) were added to 100 parts by mass of distilled water, and then stirred at 90°C for 1 hour to dissolve. Furthermore, 0.2 parts by mass of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., "Epomin P-1000 (product name)", weight-average molecular weight: 70000, solid content concentration: 30 wt%) were added to prepare a coating solution with a solid content concentration of 5 wt%. A laminated film was prepared using the aforementioned coating solution in the same manner as in Example 1. The laminated film of Comparative Example 1 has the following configuration. • Substrate layer: Biaxially oriented polypropylene (OPP) film layer (thickness: 20 μm) • First layer: Olefin-modified polyvinyl alcohol layer (thickness: 0.5 μm), sodium acetate concentration: 1% by weight • Second layer: Vapor-deposited aluminum layer (thickness: 50 nm)

[0054] [Comparative Example 2] Five parts by mass of polyvinyl alcohol (PVA) resin (manufactured by Kuraray Co., Ltd., "3-98 (product name)", sodium acetate concentration: 1% by weight) were added to 100 parts of distilled water and then stirred at 90°C for 1 hour to dissolve. Furthermore, 0.2 parts by mass of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., "Epomin P-1000 (product name)", weight-average molecular weight: 70000, solid content concentration: 30% by weight) were added to prepare a coating solution with a solid content concentration of 5% by weight. A laminated film was prepared using the aforementioned coating solution in the same manner as in Example 1. The laminated film of Comparative Example 2 has the following configuration. • Substrate layer: Biaxially oriented polypropylene (OPP) film layer (thickness: 20 μm) • First layer: Polyvinyl alcohol (PVA) layer (thickness: 0.5 μm), sodium acetate concentration: 1% • Second layer: Vapor-deposited aluminum layer (thickness: 50 nm)

[0055] [Comparative Example 3] A biaxially oriented polyethylene terephthalate (PET) film (thickness: 12 μm) treated with corona discharge was prepared as the base layer. Aluminum was directly deposited onto the corona discharge-treated surface of this base layer by physical vapor deposition (PVD) to form a second layer of deposited aluminum with a thickness of 50 nm, thereby obtaining the laminated film of Comparative Example 3. The laminated film of Comparative Example 3 has the following configuration. • Substrate layer: Polyethylene terephthalate (PET) film layer (thickness: 12 μm) • First layer: None • Second layer: Vapor-deposited aluminum layer (thickness: 50 nm)

[0056] [Changes in appearance after storage in a high-humidity environment] After storing each laminated film at 85°C and 85% RH for 24 hours, the change in the appearance of the second layer was visually observed and evaluated according to the following criteria. The results are shown in Table 1. A: No changes were observed in the exterior. B: Changes in appearance were observed, such as color changes and the appearance of pinholes.

[0057] [Table 1]

[0058] As shown in Table 1, the laminated film of Example 1 received an A rating for appearance change after 24 hours of storage under conditions of 85°C and 85% humidity, meaning no change in appearance was observed. On the other hand, each laminated film of the comparative example received a B rating for appearance change, indicating changes in appearance such as color change and pinhole formation in the second layer, i.e., deterioration of the second layer. The above results show that the laminated film of Example 1 according to the first embodiment suppresses the degradation of the second layer, which contains at least one selected from metals and inorganic oxides as the main component, under high humidity conditions, and therefore provides a laminated film that can further suppress the decrease in gas barrier properties. Furthermore, the laminated film of Example 1 was obtained by the manufacturing method according to the second embodiment.

Claims

1. A base layer and A first layer laminated on at least one surface of the substrate layer, A second layer is laminated on the preceding layer, The substrate layer contains a thermoplastic resin, The aforementioned first layer contains a water-soluble vinyl polymer as its main component, The sodium salt concentration in the aforementioned first layer is less than 0.2% by weight, A laminated film in which the second layer comprises at least one selected from metals and inorganic oxides as a main component.

2. The laminated film according to claim 1, wherein the second layer is a vapor-deposited film mainly composed of at least one selected from aluminum, aluminum oxide, and silicon oxide.

3. The laminated film according to claim 1 or 2, wherein the water-soluble vinyl polymer includes an olefin-modified vinyl alcohol resin.

4. The laminated film according to claim 1 or 2, wherein the layer comprises a polyalkyleneimine.

5. The laminated film according to claim 1 or 2, wherein the thermoplastic resin is a polyolefin resin.

6. The laminated film according to claim 1 or 2, wherein the thickness of the single layer is 0.2 to 4.0 μm.

7. Furthermore, the laminated film according to claim 1 or 2 comprises a protective layer laminated on the second layer.

8. A laminated film according to claim 1 or 2, which is a packaging film.

9. A method for manufacturing a laminated film according to claim 1 or 2, Laminating the first layer onto at least one surface of the substrate layer, A manufacturing method comprising laminating the second layer on the first layer.

10. The manufacturing method according to claim 9, wherein the sodium salt concentration in the first layer is less than 0.2% by weight.

Citation Information

Patent Citations

  • Multilayer base material, multilayer film provided with the multilayer base material, multilayer body provided with the multilayer film, and packaging material provided with the multilayer body

    JP2021024136A